ACADEMIC DISHONESTY AMONG UNDERGRADUATES OF ODUDUWA UNIVERSITY, IPETU-MODU, NIGERIA: MODERATING ROLES OF PERSONALITY TRAITS AND TASK VALUE - Adeniyi Wasiu Olasunkanmi (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The thrust of the study was to investigate the level of academic dishonesty among undergraduate students of Oduduwa University, Ipetu-modu, Nigeria, and to examine the factors that could predispose students to academic dishonesty. These were with a view to providing information on the factors that could predispose students to academic dishonesty. The study employed the survey research design. A sample of 500 students was selected for the study using a multistage sampling procedure. An adapted instrument titled “Questionnaire on Personality Traits, Task Value and Students’ Academic Dishonesty (QPTSA) was used to collect data from the students. The results showed that there was a low level of involvement in academic dishonesty among the students 286(57.5%). It was showed there was a significant relationship between extraversion (β = .051, p < 0.05), agreeableness (β = .131, p < 0.05), neuroticism (β = .327, p < 0.05), openness (β = .002, p < 0.05) and academic dishonesty, while a negative relationship existed between conscientiousness (β =.-264, p > 0.05) and academic dishonesty. Lastly, the result showed that there was a negative correlation between task value and academic dishonesty among undergraduate students (r = -.028, p >0.05). It was concluded that the incident of academic dishonesty was low among the students in the study area. However, neuroticism, extraversion, agreeableness, and openness were responsible for the academic dishonesty among the students in the study area.